1. $(p \land q ) \iff (r \implies s)$

  2. $(s \vee \neg t)$

So, $\neg s \implies ((r \implies \neg p) \vee \neg t)$

My lecturer has written in our notes that this statement is invalid, but I'm not so sure. I've attached my workings and have found there to be a contradiction whilst using the 'no counterexample' method (i.e. assume the premise to be T whilst the conclusion F, if there is a contradiction then the statement is valid) to find the validity of this statement. Thus, I think this inference is valid.

My question is: is the above inference valid or not?

Thank you so much in advanced for your help! :)

My workings out


We will follow the instructor's notes and assume that the inference is invalid.

This means : assume the premises T and the conclusion F.

We may rewrite the conclusion as :

$s \lor \lnot r \lor \lnot p \lor \lnot t \ $;

in order to have it F we need :

$s=$ F and $r=p=t=$ T.

With this truth-assignment, the second premise : $s \lor \lnot t$ would be F.

Thus, the argument is valid.

If instead the sought conclusion is : $¬s \to ((r \to ¬p) \land ¬t)$, with the same approach we have two possibilities in order to "falsify" it; either :

(i) $s=$ F and $t=$ T, or :

(ii) $s=$ F and $r=p=$ T.

In the first case, again, we cannot satisfy the second premise.

In the second case, we have two variables "undefined" : $t$ and $q$.

The two premises are equivalent to :

$($ T $\land q) \leftrightarrow$ F

F $\lor \lnot t$.

Thus, if we set : $q=t=$ F, we can satisfy both premises and we have shown that the argument is invalid.

Conclusion :

Is this a valid or invalid inference?

It depends on the formula (in this case : the conclusion) ...


If s is not true, then (not t) has to be true, thus the inference is automatically true.

On a side note, I think that you may have made a typo...

  • $\begingroup$ Yes there is a typo in the notes. You can see I've circled the t:F as I keep getting t:T $\endgroup$ – Andy Oct 13 '16 at 8:37
  • $\begingroup$ p.s the typed notes are by my lecturer and the hand written notes are mine. :) $\endgroup$ – Andy Oct 13 '16 at 8:40
  • $\begingroup$ If you do not change the "and" to "or", the interference would be invalid and the counterexample is given in step 5... I think. $\endgroup$ – Ginger88895 Oct 13 '16 at 8:43
  • $\begingroup$ Hmmm, my lecturer emailed and told us to do exactly that: change the 'and' to the 'or'... I've emailed him and asked what's going on. Will update you when I have a reply from him! Thanks @user370007 for your reassurance! Been trying for ages to figure this one out :P $\endgroup$ – Andy Oct 13 '16 at 8:49
  • $\begingroup$ I'm quite interested in this too :D $\endgroup$ – Ginger88895 Oct 13 '16 at 9:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.